Allocating CSR plant functional types: the use of leaf economics and size traits to classify woody and herbaceous vascular plants. (8th April 2013) - Pierce, Simon; Brusa, Guido; Vagge, Ilda; Cerabolini, Bruno E. L.
Summary: Three main directions of adaptive specialization are evident in the world flora, reflecting fundamental trade‐offs between economics (conservative vs. acquisitive investment of resources) and size. The current method of ordinating plants according to these trade‐offs, CSR classification, cannot be applied to the woody species that dominate many terrestrial ecosystems. We aimed to produce a novel CSR classification method applicable to vascular plants in general. Principal components analysis (PCA) of variation in a range of plant traits for 678 angiosperm, gymnosperm and pteridophyte species was used to determine the limits to multivariate space occupied by functionally diverse species. From this calibration, correlations between PCA axes and values of leaf dry matter content (LDMC; as an index of conservatism in life history), specific leaf area (SLA; indicative of acquisitive economics) and leaf area (LA; photosynthetic organ size) were used to produce predictor regressions from which target species could be compared against the multivariate space. A spreadsheet was developed that returned ternary coordinates and tertiary CSR strategies for target subjects based on LA, LDMC and SLA values. The method allowed classification of target species within a triangular space corresponding to Grime's theoretical CSR triangle and was sufficiently precise to distinguish strategies between species within genera and within populations of species. It was also largely in agreement with previous methods of CSR classification for herbaceous species. Rapid CSR classification of woody and herbaceous vascular plants is now possible, potentially allowing primary plant functional types and ecosystem processes to be investigated over landscape scales. Abstract : Lay Summary Abstract :